2019
DOI: 10.3390/pharmaceutics11090430
|View full text |Cite|
|
Sign up to set email alerts
|

Folic Acid and PEI Modified Mesoporous Silica for Targeted Delivery of Curcumin

Abstract: Nano anti-cancer drug carriers loaded with antineoplastic drugs can achieve targeted drug delivery, which enriches drugs at tumor sites and reduces the toxic side effects in normal tissues. Mesoporous silica nanoparticles (MSN) are good nano drug carriers, as they have large specific surface areas, adjustable pore sizes, easily modifiable surfaces, and good biocompatibility. In this work, polyethyleneimine (PEI) grafted MSN were modified with folic acid (FA) as an active target molecule using chemical methods.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(42 citation statements)
references
References 35 publications
(35 reference statements)
1
41
0
Order By: Relevance
“…The result intuitively shows that the uptake of FA-AmCS-TPP nanoparticles by tumor cells was significantly higher than that of AmCS-TPP nanoparticles. This confirms that the introduction of FA into the carriers can increase the uptake rate by cancer cells, which is consistent with previous reports [65,66,67,68,69].…”
Section: Resultssupporting
confidence: 93%
“…The result intuitively shows that the uptake of FA-AmCS-TPP nanoparticles by tumor cells was significantly higher than that of AmCS-TPP nanoparticles. This confirms that the introduction of FA into the carriers can increase the uptake rate by cancer cells, which is consistent with previous reports [65,66,67,68,69].…”
Section: Resultssupporting
confidence: 93%
“…DDSs have the ability to improve the biological activity, enhance the therapeutic index or extend the biological half-life of drugs [ 2 , 3 ]. Various materials including microspheres, mesoporous, micro/nanoparticles, liposomes, micelles, and emulsions were developed as effective drug carriers [ 4 ]. Currently, a wide range of nanoparticles are being advanced to serve as potential carriers for delivering drugs in a controlled mode to specific-targeted sites in the human body [ 5 , 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…1,3,9 A substantial number of studies have reported the applications of MSNs as drug carriers, and the use of MSNs as drug carriers have been proven to be successful in vitro. [6][7][8][10][11][12] To the best of our knowledge, the efficacy of MSN carriers is decided by the structural features which determine the physicochemical properties of MSNs, including shape, size, pore characteristics, and surface chemistry. 13 Along with great progress in the structure control and multi-functionalization design of MSNs, various drug delivery formulations such as immediate drug delivery systems, sustained drug delivery systems, controlled drug delivery systems, targeted drug delivery systems, and stimuli-responsive drug delivery systems have been developed to improve the dissolution and bioavailability of poorly water-soluble drugs and enhance their therapeutic potential.…”
Section: Introductionmentioning
confidence: 99%
“…13 Along with great progress in the structure control and multi-functionalization design of MSNs, various drug delivery formulations such as immediate drug delivery systems, sustained drug delivery systems, controlled drug delivery systems, targeted drug delivery systems, and stimuli-responsive drug delivery systems have been developed to improve the dissolution and bioavailability of poorly water-soluble drugs and enhance their therapeutic potential. [9][10][11][12]14,15 It should be noted that, a slight change in structural features of MSNs may not only significantly influence their host-guest interactions with drug molecules, but also impact the biological binding ability with tissues and cells. 4,16 For example, Lu et al demonstrated that decreasing the size of NPs (from 50-280 nm) is an effective way to facilitate the cell uptake of MSNs.…”
Section: Introductionmentioning
confidence: 99%